The autoimmune ecology: An update (2018)
Purpose of review The autoimmune ecology refers to the interactions between individuals and their environment leading to a breakdown in immune tolerance and, therefore, to the development of one or more autoimmune diseases in such an individual. Herein, an update is offered on four specific factors associated with autoimmune diseases, namely, Vitamin D, smoking, alcohol and coffee consumption from the perspective of exposome and metabolomics. Recent findings Smoking is associated with an increased risk for most of the autoimmune diseases. Carbamylation of proteins as well as NETosis have emerged as possible new pathophysiological mechanisms for rheumatoid arthritis. Low-to-moderate alcohol consumption seems to decrease the risk of systemic lupus erythematosus and rheumatoid arthritis, and studies of vitamin have suggested a beneficial effect on these conditions. Coffee intake appears to be a risk factor for type 1 diabetes mellitus and rheumatoid arthritis and a protective factor for multiple sclerosis and primary biliary cholangitis. Summary Recent studies support the previously established positive associations between environmental factors and most of the autoimmune diseases. Nevertheless, further studies from the perspective of metabolomics, proteomics and genomics will help to clarify the effect of environment on autoimmune diseases. © Copyright 2018 Wolters Kluwer Health, Inc. All rights reserved.